2019
DOI: 10.1101/cshperspect.a034173
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation and the Cardiovascular System

Abstract: The vagus nerve plays an important role in maintaining physiological homeostasis, which includes reflex pathways that regulate cardiac function. The link between vagus nerve activity and the high-frequency component of heart rate variability (HRV) has been well established, correlating with vagal tone. Recently, vagus nerve stimulation (VNS) has been investigated as a therapeutic for a multitude of diseases, such as treatment-resistant epilepsy, rheumatoid arthritis, Crohn's disease, and asthma. Because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 107 publications
0
78
0
1
Order By: Relevance
“…Electrocardiographic (ECG) metrics are considered to be among the most promising candidate biomarkers (Clancy et al, 2014;Gurel et al, 2020), for two reasons: Firstly, ECG is inexpensive, and quickly and safely applicable in virtually all patient subpopulations, unlike, for example, magnetic resonance imaging-based biomarkers (Mithani et al, 2019;Yakunina et al, 2017). Secondly, there is a clear physiological rationale for a relationship between taVNS and cardiac readouts, since the vagus nerve is involved in the autonomic regulation of heart rate (HR), heart rate variability (HRV) and blood pressure (BP) (Capilupi et al, 2019;Karemaker, 2015). Accordingly, animal studies have confirmed cardiac effects of (invasive) VNS (Brack et al, 2004;Brown and Eccles, 1934;Buschman et al, 2006;Iwao et al, 2000;Kuo et al, 2005;Levy et al, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Electrocardiographic (ECG) metrics are considered to be among the most promising candidate biomarkers (Clancy et al, 2014;Gurel et al, 2020), for two reasons: Firstly, ECG is inexpensive, and quickly and safely applicable in virtually all patient subpopulations, unlike, for example, magnetic resonance imaging-based biomarkers (Mithani et al, 2019;Yakunina et al, 2017). Secondly, there is a clear physiological rationale for a relationship between taVNS and cardiac readouts, since the vagus nerve is involved in the autonomic regulation of heart rate (HR), heart rate variability (HRV) and blood pressure (BP) (Capilupi et al, 2019;Karemaker, 2015). Accordingly, animal studies have confirmed cardiac effects of (invasive) VNS (Brack et al, 2004;Brown and Eccles, 1934;Buschman et al, 2006;Iwao et al, 2000;Kuo et al, 2005;Levy et al, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…5A). VNS can decrease chronotropy, afterload, and myocardial oxygen demand (Capilupi et al, 2020; Levy & Schwartz, 1994; Buck et al, 1981), all factors that are elevated during spontaneous myocardial ischemia (Svensson et al, 2001; Rehman et al, 1997; Deedwania & Carbajal, 1992; Hinderliter et al, 1991; Deedwania & Nelson, 1990). D+NE targets catecholamine receptors relevant for myocardial ischemia and has a maximal effect on the recorded features.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we used an ANN that rapidly decodes events of spontaneous myocardial ischemia, and responsively triggers therapeutic closed-loop vagus nerve stimulation (VNS). Responsive closed-loop VNS may be an effective bioelectronic medicine for reversing ischemia mediated elevations in chronotropy, afterload, and myocardial oxygen demand (Capilupi et al, 2020; Levy & Schwartz, 1994; Ardell et al, 2015; Buck et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The vagus nerve innervates the heart (93). Heart failure ultimately leads to a requirement for heart transplantation (94).…”
Section: Elevated Pns Activitymentioning
confidence: 99%
“…Interestingly, VNS was reported to be an effective clinical treatment for medication-resistant epileptic patients and depressed patients (75,101). However, clinical testing is still required to determine the efficacy of VNS in patients with cerebrovascular disease, as serious adverse cardiovascular effects are possible with VNS (93). In summary, PNS activation can improve clinical outcomes, and may represent a new direction for prevention and therapy of stroke-related ANS dysfunction.…”
Section: Elevated Pns Activitymentioning
confidence: 99%